Degradation of cyclin B is critical for nuclear division in Trypanosoma brucei - Hayashi, H; Akiyoshi, B (Company of Biologists, 2018)
Kinetoplastids have a nucleus that contains the nuclear genome and a kinetoplast that contains the mitochondrial genome. These single-copy organelles must be duplicated and segregated faithfully to daughter cells at each cell division. In Trypanosoma brucei, although duplication of both organelles starts around the same time, segregation of the kinetoplast precedes that of the nucleus. Cytokinesis subsequently takes place so that daughter cells inherit a single copy of each organelle. Very little is known about the molecular mechanism that governs the timing of these events. Furthermore, it is thought that T. brucei lacks a spindle checkpoint that delays the onset of nuclear division in response to spindle defects. Here we show that a mitotic cyclin CYC6 has a dynamic localization pattern during the cell cycle, including kinetochore localization. Using CYC6 as a molecular cell cycle marker, we confirmed that T. brucei cannot delay the onset of anaphase in response to a bipolar spindle assembly defect. Interestingly, expression of a stabilized form of CYC6 caused the nucleus to arrest in a metaphase-like state without preventing cytokinesis. We propose that trypanosomes have an ability to regulate the timing of nuclear division by modulating the CYC6 protein level, without a spindle checkpoint.